In vivo Antiplasmodial of the Most Active Fraction and Its Compound of Kapur Leaves (Harmsiopanax aculeatus Harms) Extract Against Plasmodium berghei - Rachel Turalely; Ratna Asmah Susidarti; Mahardika Agus Wijayanti (Tropical Medicine Journal, 2011)
Introduction : The rising of Plasmodium resistance towards chloroquine and other antimalarial drugs have encouraged to discover and develop new drugs mainly derived from natural products. Harmsiopanax aculeatus (kapur plant) has traditionally used by people of in Maluku Province to treat malaria.Objectives: The aims of this study were to identify antiplasmodial activity and its chemical constituents of the most active fraction of kapur leaves.Methods: The dried powder of Kapur leaves (1.3 kg) were extracted successively by maceration with n-hexane, ethyl acetate and methanol. After removal the solvents the hexane 15.6 g (1.2%), ethyl acetate 53.3 g (4.1%) and methanol 61.1 g (4.7%) extracts were obtained. Those extracts were assayed for their in vivo antiplasmodial activities by using 4-days suppressive test in Swiss mice infected with Plasmodium berghei, HPIA and identified the compound by GC-MS.Results: The ED50 of hexane, ethyl acetate and methanol extracts were 467.58, 2074.02 and 16.16 mg/kgBW, respectively. Fractionation of the methanol extract gave 18 combined fractions (FG1 – FG18). FG8 was the most active fraction with the IC50 HPIA of 18.22 μg/ml. Phytochemical test of this fraction using spray reagent showed the existence of essential oils, triterpenoids, and phenolic compounds. Separation of FG8using pressed chromatography gave 19 combined fractions (FG8.1-FG8.19). The fraction containing intense blue fluorescent spot (FG8.5) was further separated by PLC fourthly eluted with chloroform. Seven major components with the percentage of compotition more than 3.11% were identified as eugenol (tr = 12.692; 18.22%), isoprophyl myristate (tr = 16.333; 3.99%); bis(2-methylpropyl) phtalat (tr = 16.939; 7.15%); methyl palmitic (tr = 17.442; 3.11%); palmitic acid (tr = 17.883; 25.72%); butyl 2-methylpropyl phtalat (tr = 17.957; 9.37%) and bis(2-ethylhexyl) phtalat (tr = 23.258; 23%).Conclusion: Methanol extract of H. aculeatus was the most potential in vivo antiplasmodial activity. Combined fraction 8 which contain 7 compounds was the most active fraction.Keywords: Harmsiopanax aculeatus Harms, in vivo antiplasmodial, HPIA, PLC, GC-MS